MANAJEMEN STRATEJIK PADA PERUSAHAAN GITA GROUP - Fransisko Gemanta Poerba; Christina Ayuningtyas; Irham A. Dilmy (Journal of Business Strategy and Execution, 2008)
Gita Group Company, consisting of PT. Sagita Raya Transport Service, PT. Gita Terminal Sarana (GTS) dan PT. Gita Tata Ekspresindo (GTE), is having significant problems in which the management feels the needs to conduct evaluation, alteration and repairment in some areas. The purpose of this project is to find what and where the problems actually are and give suggestions to the management on how to solve them. Results shows that there is no clear line to limit and standardise the management policies, an almost non-existence of routine evaluations such as work evaluation and financial evaluation, standard operational procedures, and unclear pricing-cost-service management as well as no definitions of the company’s vision and mission. Therefore, suggestions will be made by presenting steps that are possible to be implemented within the internal management starting from planning and formulating necessary changes and standardisations, communicating and applying these changes to directing the company towards its targets or goals.